Ответы 2

  • sin(x/2- π/6)+1=0

    1 = sin(π/2)

    sin(x/2 - π/6) + sin(π/2) = 0

    sin(x/2 - π/6) = -sin(π/2) 

    sin(x/2 - π/6) = sin(-π/2)

    x/2 - π/6 = (3x - π)/6

    (3x - π)/6 = -π/2

    3x - π + 3π = 0

    3x +2π = 0

    3x = -2π

    x = -2π/3

    Ответ: -2π/3

     

    • Автор:

      compton
    • 5 лет назад
    • 0
  • sin(x/2- π/6)+1=0

    sin(x/2- π/6)= -1

    x/2- π/6 = -π/2 + 2πn

    x/2 = π/6-π/2 + 2πn

    x/2 = -2π/6 + 2πn

    x = -2π/3 + 4πn

    • Автор:

      punkypvl
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years